Post-Mortem Bronchopulmonary and Cardiovascular Histopathological Finding in Patients who Died of Interactable Asthma Attack with Synchronous Paecilomyces Infection - Sizova, Zhana M; Akhunov, Vasili M; Azimzadeh, Amir A; Lavrentieva, Tatyana P (Cardiology and Cardiovascular Medicine, 2021)
Objective: The potential histopathological changes of Paecilomyces infection in bronchopulmonary and cardiovascular system of patients with bronchial asthma is evaluated on the postmortem tissue specimens. Methods: Postmortem histopathological evaluation of cardiopulmonary system is performed in 15 patients (5 women and 10 men, aged between 18-77 years old). All the patient’s died as a result of intractable asthma attacks and acute cardiovascular insufficiency. Hematoxylin and Eosin-stained paraffin sections of bronchopulmonary and cardiovascular systems are examined. Special methods are employed to detect fungi and the tissue. Results: Microscopic examination in the lungs revealed vascular congestion, extension of venules and capillaries, arteriolar spasm, endothelial inflammation with a tendency to desquamation, and increased permeability of the vascular wall with fungal cells in the perivascular space. Changes in vascular walls were characterized by a pattern of destructive-productive vasculitis at different stages of development from endovascular to perivascular space inflammation resulting in sclerosis. The same type of changes was found in vascular walls of other organs including the heart, resembling different stages of the process. Sclerosis of the vascular wall and the perivascular tissue may represent a protective inflammatory response to limit the spread of the pathogen. Conclusions: Our data suggests that the complex vascular pathology in the cardiopulmonary system in patients with bronchial asthma may be triggered by a hematogenic infection caused by dimorphic Paecilomyces fungi.